Geological storage potential of CO2 emissions for China's coal-fired power plants: A city-level analysis. (March 2021) - Fan, Jing-Li; Wei, Shijie; Shen, Shuo; Xu, Mao; Zhang, Xian
Highlights: Geological storage potential of CO2 emissions for China's coal-fired power plants is estimated. Daqing, Ordos and Bayin'gholin Mongol have the largest CO2 storage capacity of enhanced water/oil/gas recovery respectively. The mismatch of coal-fired power plants and CO2 storage sites restrict the emission reduction potential of cities in China. Ordos has the largest CO2 emission reduction potential through CO2 geological storage projects of coal-fired power plants. Abstract: To mitigate global warming to temperatures no higher than 2 °C or even less than 1.5 °C, carbon capture and storage (CCS) is indispensable. This is especially true for China, which relies heavily on coal-fired power plants. In China, CCS could play an important role in removing CO2 emissions from coal-fired power plants and establishing low-carbon cities. Clarifying the emissions reduction potential of cities using CO2 geological storage will help to identify site suitable for carrying out CCS projects in a technically and economically feasible way. In this paper, we assessed CO2 storage capacity in three geological structures between 800 to 3000 m underground: (1) the nationwide on-shore CO2 storage capacity of 705 oil fields in terms of both depleted oil reservoirs (DOR) and enhanced oil recovery (EOR); (2) 754 gas fields in terms of both depleted gas reservoirs (DGR) and enhanced gas recovery (EGR); (3) China's deep saline aquifers (DSA), including 17 large basins ; and (4) the CO2 emissions of coal-fired plants of 300 MW and over. After completing all of these assessments, this paper presents an emissions reduction potential estimate. The results show that: 1) the total CO2 storage capacity of DOR, EOR, DGR, EGR and DSA is 21, 287 Mt, 5191 Mt, 15, 321 Mt, 9018 Mt and 1, 004, 319 Mt, respectively; 2) 76 cities can sequester their existing CO2 emissions from coal-fired power plants in situ within their administrative boundaries for over 10 years, and their contribution is 634.43 Mt per year. 3) Ordos City has priority to carry out CO2 geological storage for coal-fired power plants due to the volume of its annual captured CO2 (52.13 Mt), and it can operate for about 123 years if its CO2 emissions remain unchanged.